Clinical Efficacy and Safety of Vitaros©/Virirec© (Alprostadil Cream) for the Treatment of Erectile Dysfunction. Issue 2 (April 2015) - Moncada, Ignacio; Cuzin, Béatrice
Erectile dysfunction (ED) is a very common disorder with a deep impact on patients and their partners. Several options are now available for treating ED; oral pharmacotherapy with phosphodiesterase-5 (PDE5) inhibitors currently represents the first-line option for many ED patients. Vitaros © /Virirec © is new topical, non-invasive treatment for ED that offers the combination of an active drug (alprostadil, a synthetic PGE1) with a skin enhancer that improves its local absorption directly at the site of action. Vitaros © /Virirec © has a favorable pharmacodynamic profile and is poorly absorbed in systemic circulation. This makes it suitable in any circumstances and results in a reduced risk of adverse events (AEs), being systemic AEs reported in only 3% of the treated population. Its clinical efficacy has been demonstrated in both phase II and III trials, showing a global efficacy up to 83% with the 300 μg dose in patients with severe ED significantly better than placebo. Its fast onset of action together with its favorable toxicity profile and lack of interactions with other drugs makes Vitaros © /Virirec © a first-line therapeutic option for patients with ED, particularly for individuals who are reluctant to take systemic treatments or with AEs. It may also have an important role in patients not responding to PDE5 inhibitors, particularly those with ED after radical prostatectomy.